1991
DOI: 10.1161/01.atv.11.4.1030
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) and apolipoprotein(a) in a New World monkey, the common marmoset (Callithrix jacchus). Association of variable plasma lipoprotein(a) levels with a single apolipoprotein(a) isoform.

Abstract: In an earlier report (Chapman et al, Biochemistry 1979;18:5096-5108), we suggested that the common marmoset may represent an important model for the study of human plasma lipoprotein metabolism. We now extend the interest of this monkey model to the study of lipoprotein(a) (Lp[a]) and apolipoprotein(a) (apo[a]). Density gradient ultracentrifugal fractionation of marmoset plasma revealed a bimodal distribution of Lp(a), with one peak of concentration occurring in association with very low density lipoproteins (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In this article we have evaluated the segregation of the apo(a) gene and plasma Lp(a) levels in 48 Caucasian families and found that virtually all the inter-individual variation in plasma Lp(a) levels was attributable to the genomic region encoding the apo(a) glycoprotein. It had been clear from previous family studies that plasma Lp(a) levels are largely genetically determined; prior estimates of the heritability of plasma Lp(a) levels have ranged from 0.75 to 0.98 (15,17,40,41) which is comparable to our estimate of 0.85 (±8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article we have evaluated the segregation of the apo(a) gene and plasma Lp(a) levels in 48 Caucasian families and found that virtually all the inter-individual variation in plasma Lp(a) levels was attributable to the genomic region encoding the apo(a) glycoprotein. It had been clear from previous family studies that plasma Lp(a) levels are largely genetically determined; prior estimates of the heritability of plasma Lp(a) levels have ranged from 0.75 to 0.98 (15,17,40,41) which is comparable to our estimate of 0.85 (±8%).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma Lp(a) concentrations were measured in a sample of 288 fasting individuals from 48 Caucasian American families living in the greater Dallas, Texas area. Families in which both parents and at least three children were available for sampling were selected for study.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is far from a linear relationship between small size of the Lp(a) polypeptide chain and high concentration of Lp(a) lipoprotein in serum. Thus, a 100-fold variation in Lp(a) lipoprotein concentration (0.5-49 mg/dl plasma) has been reported in a primate that exhibited only one molecular size of the Lp(a) polypeptide chain (Guo et al 1991). Also, Hobbs and her co-workers have reported evidence that a specific gene (DraIII pattern 3) with a low number of kringle IV repeats is invariably associated with low concentration of Lp(a) lipoprotein (Mancini et al 1995).…”
Section: Lsoforms Of the Lp(a) Polypeptide Chain And Disease Riskmentioning
confidence: 97%
“…It is a small sidebar but also important to point out that when you are uncertain as to what you are measuring and sometimes even when you are, interference from the drug or its metabolites can affect the performance of the assay and the level of the analyte you are trying to measure (4). In defense of the authors, it might be well to point out that this is not the first time that Lp(a) has been reported in a species where the data were not reproducible by other investigators (5,6). All of this is not so cut and dry.…”
Section: Information On the Standardization Of The Assay Is Especiall...mentioning
confidence: 72%